Gagasan ‘Islamic Security’ untuk Konflik Global - Minardi, Anton (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
Islam is an integralistic system in science and action where no separation between Allah’s direction with environment management dan human, can be solution for every conflicts. Conflict always happen caused by error of thought and human unpatience. Islam in this case gives best solution for international conflict as securitization toward various natural resourches with Islamic direction including human rights, environment, economic, political, and military.